The Limits to Union Same-Sex Marriage and the Politics of Civil Rights - Goldberg-Hiller, Jonathan (University of Michigan Press, 2002)
From its legal recognition in Hawaii in 1993, the idea and possibility of same-sex marriage has been a fuse that has ignited political controversy across the United States to the world. This controversy sets forces championing the expansion of court-ordered rights against conservative and religious partisans who no longer accept the rationale for expanding civil rights. The Limits to Union explores this incendiary debate and explains the political discourses and tactics that overturn decisions of state courts favorably inclined toward same-sex marriage and gay rights. The opposition of public majorities to court-mandated rights is shown to be an enduring yet postmodern manifestation of political sovereignty, one with broad implications for how we must now come to think about civil rights.